Research progress in isolation and identification of rumen probiotics - Wu, Runmin; Ji, Peng; Hua, Yongli; Li, Hongya; Zhang, Wenfei; Wei, Yanming (Frontiers in Cellular and Infection Microbiology, 2024)
With the increasing research on the exploitation of rumen microbial resources, rumen probiotics have attracted much attention for their positive contributions in promoting nutrient digestion, inhibiting pathogenic bacteria, and improving production performance. In the past two decades, macrogenomics has provided a rich source of new-generation probiotic candidates, but most of these "dark substances" have not been successfully cultured due to the restrictive growth conditions. However, fueled by high-throughput culture and sorting technologies, it is expected that the potential probiotics in the rumen can be exploited on a large scale, and their potential applications in medicine and agriculture can be explored. In this paper, we review and summarise the classical techniques for isolation and identification of rumen probiotics, introduce the development of droplet-based highthroughput cell culture and single-cell sequencing for microbial culture and identification, and finally introduce promising cultureomics techniques. The aim is to provide technical references for the development of related technologies and microbiological research to promote the further development of the field of rumen microbiology research.